2022
DOI: 10.1021/acsami.2c13834
|View full text |Cite
|
Sign up to set email alerts
|

High-Sensitivity Microthermometry Method Based on Vacuum-Deposited Thin Films Exhibiting Gradual Spin Crossover above Room Temperature

Abstract: We report on the fabrication, characterization, and microthermometry application of high-quality, nanometric thin films, with thicknesses in the range 20–200 nm, of the molecular spin-crossover complex [Fe­(HB­(1,2,3-triazol-1-yl)3)2]. The films were obtained by vacuum thermal evaporation and characterized by X-ray diffraction, UV spectrophotometry, and atomic force microscopy. The as-deposited films are dense and crystalline with a preferred [011] orientation of the monoclinic crystal lattice normal to the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Film thicknesses were monitored in situ using a quartz crystal microbalance and ex situ by spectral reflectance measurements (Filmetrics, F20). The as-deposited films of 1 are dense and crystalline with a preferred [011] orientation of the monoclinic crystal lattice normal to the substrate surface . The as-deposited films of 2 were recrystallized by a solvent-vapor annealing treatment, resulting in oriented, nanocrystalline thin films …”
Section: Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Film thicknesses were monitored in situ using a quartz crystal microbalance and ex situ by spectral reflectance measurements (Filmetrics, F20). The as-deposited films of 1 are dense and crystalline with a preferred [011] orientation of the monoclinic crystal lattice normal to the substrate surface . The as-deposited films of 2 were recrystallized by a solvent-vapor annealing treatment, resulting in oriented, nanocrystalline thin films …”
Section: Experimental Methodsmentioning
confidence: 99%
“…The as-deposited films of 1 are dense and crystalline with a preferred [011] orientation of the monoclinic crystal lattice normal to the substrate surface. 38 The as-deposited films of 2 were recrystallized by a solvent-vapor annealing treatment, resulting in oriented, nanocrystalline thin films. 37 Spectroscopic Characterization.…”
Section: Spin-crossover Sample Synthesis and Opticalmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of temperature sensors attracts much attention in various fields with the advent of numerous methods developed for accurate temperature measurements at nano- and microspatial resolutions and in various conditions. In particular, noninvasive methods, e.g., infrared (IR), optical, and luminescence thermometry, can be useful in determining the temperature of certain conditions, such as high temperatures or chemically reactive flames or plasmas. , Additionally, the rarely explored Raman spectroscopy is emerging as a valuable tool for thermometry with the advantages of carrying out nondestructive and noncontact measurements with high spatial resolution on micrometer-sized crystals, thin films, nanoparticles, and powder samples. , Temperature variations can be determined by following the changes in intensity, width of the peak signals, and peak position. Recently, the above thermometric concepts have been extended to spin-crossover (SCO) materials by characterizing various properties, e.g., optical reflectivity, , thermochromic properties, , magnetic resonance imaging, and fluorescence. , They suggested that SCO materials can provide a universal platform for thermometric studies due to their versatile tunability and switching effects.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Temperature variations can be determined by following the changes in intensity, width of the peak signals, and peak position. Recently, the above thermometric concepts have been extended to spin-crossover (SCO) materials by characterizing various properties, e.g., optical reflectivity, 11,12 thermochromic properties, 13,14 magnetic resonance imaging, 15 and fluorescence. 16,17 They suggested that SCO materials can provide a universal platform for thermometric studies due to their versatile tunability and switching effects.…”
Section: ■ Introductionmentioning
confidence: 99%